2005
DOI: 10.1517/14728222.9.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Treating the metabolic syndrome: acetyl-CoA carboxylase inhibition

Abstract: Metabolic syndrome is defined as a clustering of cardiovascular risk factors (abdominal obesity, hyperinsulinaemia, atherogenic dislipidaemia, hypertension, hypercoagulability) that together increase the risk of developing coronary heart disease and Type-2 diabetes. Inhibition of acetyl-CoA carboxylase (ACC), with its resultant inhibition of fatty acid synthesis and stimulation of fatty acid oxidation, has the potential to favourably affect, in a concerted manner, a multitude of cardiovascular risk factors ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
114
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 81 publications
0
114
0
Order By: Relevance
“…Finally, ACC1 and its isoform ACC2 have become pharmaceutical targets, of concern for the inhibition of lipid accumulation and the prevention of hepatic steatosis and obesity (18,19). Present results showed that inactivation of ACC1could not protect the mice against diet-induced obesity or hepatic steatosis.…”
Section: Facc1ko Mice Show Decreased Osteoblastogenesismentioning
confidence: 71%
See 1 more Smart Citation
“…Finally, ACC1 and its isoform ACC2 have become pharmaceutical targets, of concern for the inhibition of lipid accumulation and the prevention of hepatic steatosis and obesity (18,19). Present results showed that inactivation of ACC1could not protect the mice against diet-induced obesity or hepatic steatosis.…”
Section: Facc1ko Mice Show Decreased Osteoblastogenesismentioning
confidence: 71%
“…ACC1 has been thought to be a good target for the drug treatment of obesity (18,19). To test whether the disruption of ACC1 in adipose tissues would inhibit diet-induced obesity, 2-month-old male mice were fed a high fat/high carbohydrate (HF/HC) diet for 10 weeks.…”
Section: Facc1ko Mice Show Decreased Osteoblastogenesismentioning
confidence: 99%
“…Furthermore, these changes were not associated with any changes in plasma concentrations of IL-6, TNF-␣, adiponectin, or resistin, suggesting that these adipocytokines were not involved in mediating insulin resistance in this mouse model. Several pharmacological attempts have been made to inhibit ACC (40). Major difficulties have included problems in generating ACC isoform specific inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hyperinsulinemia and/or glucocorticoid excess might cause accumulation of triglyceride partly via the effects of the two hormones on ACC1/2 expression. In this context, pharmacological inhibition of ACC might be a promising therapeutic tool for the prevention of abdominal obesity frequently observed in the metabolic syndrome [36,37].…”
Section: The Effects Of Lxrα/β Co-expression On the Transcriptional Amentioning
confidence: 99%